2001
DOI: 10.1038/sj.bjp.0703926
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of 2,3‐butanedione monoxime (BDM) on Na+/Ca2+exchange current in guinea‐pig cardiac ventricular myocytes

Abstract: 1 The eect of 2,3-butanedione monoxime (BDM), a`chemical phosphatase', on Na + /Ca 2+ exchange current (I NCX ) was investigated using the whole-cell voltage-clamp technique in single guinea-pig cardiac ventricular myocytes and in CCL39 ®broblast cells expressing canine NCX1. 2 I NCX was identi®ed as a current sensitive to KB-R7943, a relatively selective NCX inhibitor, at 140 mM Na + and 2 mM Ca 2+ in the external solution and 20 mM Na + and 433 nM free Ca 2+ in the pipette solution.3 In guinea-pig ventricula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 40 publications
4
48
0
Order By: Relevance
“…However, the inhibitory effect of BDM on I NCX is not affected by okadaic acid. In addition, BDM inhibits both I NCX from CCL39 cells expressing NCX1 and its mutant in which three major phosphorylatable serine residues are replaced with alanine (55). We conclude that the mechanism of inhibition of BDM is not by dephosphory- lation of NCX as a chemical phosphatase.…”
Section: Other Antiarrhythmic Drugs (Dronedarone Cibenzoline and Azmentioning
confidence: 76%
See 1 more Smart Citation
“…However, the inhibitory effect of BDM on I NCX is not affected by okadaic acid. In addition, BDM inhibits both I NCX from CCL39 cells expressing NCX1 and its mutant in which three major phosphorylatable serine residues are replaced with alanine (55). We conclude that the mechanism of inhibition of BDM is not by dephosphory- lation of NCX as a chemical phosphatase.…”
Section: Other Antiarrhythmic Drugs (Dronedarone Cibenzoline and Azmentioning
confidence: 76%
“…We conclude that the mechanism of inhibition of BDM is not by dephosphory- lation of NCX as a chemical phosphatase. The inhibitory mechanism of BDM on I NCX is unclear, but intracellular trypsin treatment almost completely abolishes the inhibitory effect of BDM (55), suggesting that BDM affects NCX at an intracellular site.…”
Section: Other Antiarrhythmic Drugs (Dronedarone Cibenzoline and Azmentioning
confidence: 99%
“…To abolish the motion artifact from recorded data, the optical mapping techniques require the use of excitation-contraction uncouplers. In the present study, we utilized BDM, which is known to change several membrane conductances (6,56) and thereby causes some electrophysiological effects (14,37,40), including flattening the APD restitution curve (3). To examine the potential effect of BDM on the dynamics of cardiac response, we conducted two additional experiments using a new excitation-contraction uncoupling agent, blebbistatin, which is considered to have no effects on the AP morphology in rabbit cardiac tissue (22).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the administration of 10-20 mM BDM in the media for cell isolation is also widely used for reducing cell damage [12,30]. However, reports have shown that BDM affects the electrophysiological and contraction properties of heart cells, as well as their Ca 2+ signaling, via direct action, protein phosphorylation, and/or altered gene expression [16,17,[31][32][33].…”
Section: Comparison With Other Heart Cell Isolation Techniquesmentioning
confidence: 99%